The Effect of Audiolyfe Stimulation on Emotional Regulation Abilities in Children, Including Tantrums, Anger, and Aggressive Behavior - Adhitya Putra Pratama (Green Publisher Indonesia, 2024)
Emotional development in children is an important aspect in the growth and development process that can affect children's behavior and social interactions. However, many children experience difficulties in controlling their emotions, which can be seen in tantrums, anger, and aggression. Audiolyfe stimulation, as an innovative approach, offers the potential to improve children's emotion control ability. This study aims to explore the effect of audiolyfe stimulation on children's emotion control ability, as well as to understand the mechanisms underlying these behavioral changes. The method used in this study was quantitative with a quasi-experimental approach. Data is collected through observation and questionnaires. The data obtained will be analyzed using descriptive statistics. The results showed that audiolyfe stimulation has an effect on children's emotional control abilities including tantrum behavior, anger, and aggression. Children who were given this stimulation showed a marked decrease in the frequency and intensity of tantrums, as well as a better ability to control anger and reduce aggressive behavior. These changes were more pronounced in the group of children who received Audiolyfe stimulation. This confirms that auditive stimulation such as Audiolyfe can be an effective method in helping children better manage their emotions.